Evaluation of heparin production by-products in nursery pig diets - Myers, A.J.; Steidinger, M.U.; Ratliff, B.W.; McKilligan, D.M.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 1,152 weanling pigs (Newsham GPK35 × PIC380, initially 12.3 ± 1.30 lb, 20 ± 2 d of age) were used in a 39-d study to evaluate the effects of select menha- den fish meal (SMFM), poultry meal, PEP2+, Peptone 50, and PEP-NS on nursery pig performance. PEP2+, Peptone 50, and PEP-NS are all porcine intestinal mucosa products, but they differ in the carriers with which they are co-dried. PEP2+ is co-dried with enzymatically processed vegetable proteins and amino acid (AA) dried fermentation biomass. Peptone 50 is co-dried with a vegetable protein, whereas PEP-NS uses by-products from corn wet-milling as well as dried fermentation biomass. Pigs were randomly allotted to 1 of 6 dietary treatments with 32 pigs per pen and 6 replications per treatment. Treatment diets were fed in 2 phases (d 0 to 7 and d 7 to 21) with a common diet fed to all pigs in the third phase (d 21 to 39). Treatments consisted of a negative control (NC) diet containing 4.5% SDAP in Phase 1 and no specialty protein sources in Phase 2 or the NC diet with 6% poultry meal (PM), PEP2+, Peptone 50, or PEP-NS. From d 0 to 21, pigs fed diets containing 6% SMFM, PM, PEP2+, or PEP-NS had improved (P < 0.05) ADG and ADFI compared with those fed the negative control diet. Pigs fed diets containing 6% SMFM, PM, PEP2+, or PEP-NS had improved (P < 0.05) F/G compared with pigs fed 6% Peptone 50. From d 21 to 39, pigs previously fed diets containing 6% PEP2+ or PEP-NS had improved (P < 0.05) ADG and ADFI compared with those previously fed the negative control diet. Overall (d 0 to 39), pigs fed diets containing 6% SMFM, PM, PEP2+, or PEP-NS had improved (P < 0.05) ADG and ADFI compared with pigs fed the negative control diet. No significant differences were observed among treatments for F/G; therefore, PEP2+ and PEP-NS are suitable replacements for fish meal and poultry meal in nursery diets from d 7 to 21 postweaning.
Keywords: Swine; Fish meal; PEP2+; Peptone 50; PEP-NS; Spray-dried animal plasma; Nursery pig